1970
DOI: 10.1042/cs0380439
|View full text |Cite
|
Sign up to set email alerts
|

Observations of Renal Function in Patients Undergoing Therapeutic Diuresis with Frusemide

Abstract: 1.Changes in extracellular water, plasma volume, blood urea and glomerular filtration rate were recorded over intervals of up to 28 days in ten patients requiring diuretic therapy, eight of whom were oedematous and none of whom had obvious renal disease.2. Diuresis with frusemide was invariably associated with a fall in extracellular water and, in all but one instance, with a fall in plasma volume. It was also associated in every case with a rise in blood urea and fall in glomerular filtration rate.3. The fall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

1974
1974
1982
1982

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…Nevertheless, under conditions where fluid correction was incomplete, suppression of GFR by furosemide was more marked in animals receiving low infusion than those with high infusion despite the similar net fluid deficit in both groups at the end of experiments. Therefore, fluid depletion alone did not seem to account for the fall in GFR (6). Clearance measurements (2) (7,8,10).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, under conditions where fluid correction was incomplete, suppression of GFR by furosemide was more marked in animals receiving low infusion than those with high infusion despite the similar net fluid deficit in both groups at the end of experiments. Therefore, fluid depletion alone did not seem to account for the fall in GFR (6). Clearance measurements (2) (7,8,10).…”
mentioning
confidence: 99%
“…The present work was undertaken to ascertain whether potent loop diuretics such as furosemide have a "washout" effect and prevent gentamicin from depositing in the renal parenchyma. Since furosemide could cause renal dysfunction by severe depletion of body fluid and electrolytes (4,6,9) ). An infusion of the same solution at 1.2 ml/h immediately followed and was continued for 3 h. Collection of blood and urine samples began 1 h after priming dose and consisted of four consecutive clearance periods of 30 min each.…”
mentioning
confidence: 99%
“…Indeed H illenbrand and Sherlock [8] suggested metolazone might be useful in patients with ascites and impaired renal function because of the low incidence of azotaemia that they noted. Better control of dietary salt intake might have prevented azotaemia occurring, although J ewkes et al [9] have shown that diuresis with frusemide invariably is associated with a fall in extracellular water, a rise in blood urea and a fall in GFR.…”
Section: Discussionmentioning
confidence: 99%
“…Mean values rose significantly after metolazone therapy (t 2.28, p. <0.05 and t 3.15, p. <0.01). Metolazone therapy was dis- continued in three patients (9,12,16) because of deterioration in renal func tion. Patients 13 and 20 showed improvement in renal function.…”
Section: Pari 2 Oral Metolazonementioning
confidence: 99%
See 1 more Smart Citation